Mortgage Interest Rates in the Populist Era - Eichengreen, Barry (American Economic Review, 1984)
Since the classic work of Solon Justus Buck (1913) on the Granger Movement, historians have attempted to critically assess the economic roots of agrarian discontent at the end of the nineteenth century.1 farmers themselves complained that the prices they received for agricultural goods had fallen because railroads and grain elevator operators were acting collusively and middlemen were restricting demand, that the prices they were charged for other commodities were being artificially inflated by suppliers with market power, and that the usurious rates charged by moneylenders on farm mortgages were impoverishing the settler in need of credit. In response, the farmers attempted to organize cooperatives to bypass middlemen and lobbied for the regulation of railroad rates and the imposition of interest rate ceilings. Early analyses of nineteenthcentury farm protest, exemplified by John Hicks (1931), while not always taking these complaints at face value, were predicated upon the assumption that farmers were suffering from deteriorating economic conditions. Subsequent writers, starting with Fred Shannon (1945), attacked the traditional interpretation. Douglass North (1966) provides a summary of the revisionist view. To the complaint that the prices of farm products were falling, he offered that other commodity prices were declining as well and that the farmer's terms of trade were actually improving. To the complaint that railroad rates were artificially inflated, he responded that the price of transportation services fell faster than the general price level, and that the spread between farm prices and market prices narrowed over the period. While admitting that a comparison of mortgage interest rates in the eastern states and the rest of the country was the one observation consonant with the farmer's position, he pointed out that it is hard to know how much of this interest differential was due not to capital market imperfections but to the greater riskiness of mortgage loans out on the frontier (see p. 142). subsequent literature went to considerable lengths to elaborate and refine these views.2 traditional economic explanations were undermined to the point where textbook descriptions presented agrarian unrest as The Puzzle of Farm Discontent (Susan Lee and Peter Passell, 1979, p. 292). Left with no explanation for the frequency with which farmers voiced complaints of distress, economic historians engaged in various attempts to rehabilitate the traditional view. Anne Mayhew (1972) portrayed farm protest * Department of Economics, Harvard University, Cambridge, MA 02138. An earlier version of this paper was presented to seminars at the University of Rochester and Baruch College. In addition to those made by seminar participants, I am grateful for the comments of Lee Alston, Peter Berck, Stephen DeCanio, Stanley Engerman, Henry Gemery, Robert Higgs, John James, William Parker, Mark Rush, James Stock, Peter Temin, Jeffrey Williams, and Jeffrey Williamson. 'In addition to Buck, see the references cited below. 2The relevant literature is too extensive to survey here. For examples, see the analysis of railroad rates in Robert Higgs (1970), of farm prices in John Bowman and Richard Keehn (1974), and of agricultural incomes in Robert Fogel and Jack Rutner (1972).